Authenticating ad hoc networks by comparison of short digests - Nguyen, L; Roscoe, A (2008)
Information and Computation. Vol. 206, Issues 2-4, Feb-Apr 2008, pp. 250-271. Special Issue of Information and Computation on Computer Security: Foundations and Automated Reasoning. Accepted in 20th July 2007, appear online in November 2007.